Internet of energy handbook - Kumar, Pawan; Nikolovski, Srete; Dong, Z Y (CRC Press, Taylor & Francis, 2021)
The Internet of Energy (IoE), with the integration of advanced information and communication technologies (ICT), has led to a transformation of traditional networks to smart systems. Internet of Energy Handbook provides updated knowledge in the field of energy management with an Internet of Things (IoT) perspective. Explains the technological developments for energy management leading to reduction in energy consumption through topics like smart energy systems, smart sensors, communication, techniques and utilizationIncludes dedicated sections covering varied aspects related to renewable sources of energy, power distribution and generation and so forthIncorporates energy efficiency, optimization and sensor technologies Covers multidisciplinary aspects in computational intelligence and IoTDiscusses building energy management aspects including temperature, humidity, number of persons involved and the light intensityThis handbook is aimed at graduate students, researchers, and professionals interested in power systems, IoT, smart grids, electrical engineering, and grid and transmission